HEINRICH HEINE AND UKRAINE: AN ATTEMPT AT AN OVERVIEW - Рудницький, Л. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The peculiarities of German poet Heinrich Heine’s lyrics and their translations into the Ukrainian language are investigated.